Mais 80s que os próprios 80s : música, nostalgia e tempo nas experiências do canal Mitch Murder - Diogo França Tomaz Aquino (2020)
This work consists of a series of reflecions woven from multiple experiences found in Mitch Murder, a YouTube channel. We start characterizing the channel itself, the musician by whom it is managed, its publications and the musical–imagetic proposition of synthwave. The Mitch Murder channel offers audiovisual publications, in addition to YouTube comments and other verbal texts. Almost every audiovisual publication involves synthwave musical pieces and a myriad of references to pop culture coming from North of the globe. YouTube commentators frequently associate productions with the 1980s, even though they were created in the twenty-first century, and carry references arising from other decades. Thus we noticed a referentiality breach over the term 80s, caused by the disjunction between the historical period and the multiple entities emerging from the channel’s publications. Trying to better understand what would be that heterogeneous set of elements, we built and adopted the notion of landscape as a interpretative category, a spaciality that can be experienced through multiple perspectives, and in which dwell human and inhumane agents. Finally, we resume the question of referentiality and discuss to what extent the idea of nostalgia is sufficiently strong to address the “80s” tag found in the Mitch Murder channel, pointing out its weaknesses and other possibilities left beside when we emphasize it.